Beyond Conventional Mating: Reviewing the Possibility of Second Pregnancies in Albino Rats without Male Access - Mansour, Samira R; Moustafa, Mostafa A; Moustafa, Mardies A; Elshazly, Amaal M; Moustafa, Abdelraouf A (Archives of Case Reports, 2025)
Background: Albino rats are extensively utilized in reproductive and biomedical research owing to their well-characterized physiology. Under normal physiological conditions, a successful pregnancy necessitates copulation with a fertile male. However, atypical cases have been documented wherein females appear to undergo a subsequent pregnancy in the absence of male contact following an initial mating event. Objective: This review aims to clarify potential biological mechanisms underlying this rare and interesting phenomenon, synthesize evidence from rodent studies and comparative biology, and discuss the implications for reproductive science in the future. Methods: A narrative review of the literature was performed, focusing on the reproductive physiology of albino rats, pseudopregnancy, sperm storage, superfetation, and parthenogenesis. Additional insights were combined from studies involving other species exhibiting similar reproductive phenomena. Results: Several mechanisms may explain the occurrence of second pregnancies in the absence of male contact: (a) sperm storage within the female reproductive tract allowing delayed fertilization; (b) hormonally induced pseudopregnancy without fertilization; (c) superfetation, defined as conception during an ongoing pregnancy; (d) accidental parthenogenesis, although this phenomenon is extraordinarily rare in mammals; and (e) experimental or housing artifacts, including overlooked male access. Evidence from rodent models predominantly supports pseudopregnancy and sperm storage as the most reasonable explanations, whereas parthenogenesis remains highly improbable in mammals. Conclusion: The observation of second pregnancies in albino rats without male presence challenges the traditional paradigm of mammalian reproduction. Although definitive evidence is currently lacking, consideration of these potential mechanisms exposes significant gaps in reproductive biology knowledge. Future studies employing genetic, hormonal, and histological approaches are needed to clarify this phenomenon and its implications for reproductive biology, laboratory animal management, and the reliability of experimental outcomes.